Immunoexpression of proteins related to apoptosis and proliferation in serous ovarian tumour - Stawerski, Paweł; Wągrowska-Danilewicz, Małgorzata; Stasikowska, Olga; Danilewicz, Marian (Menopause Review/Przegląd Menopauzalny, 2010)
Introduction: Ovarian cancer takes fourth place as a cause of death from all cancers and first place from gynaecological malignancies in Poland. Recent investigations have noted the prognostic significance of proteins linked with proliferation (Ki-67) and apoptosis (CAS – cellular apoptosis susceptibility protein). The aim of the study was to evaluate the immunoexpression of CAS and Ki-67 proteins in metastatic and non-metastatic serous ovarian tumours, as well as to find possible relationships between this immunoexpression and tumour proliferation activity. Material and methods: The analysis comprised 43 women diagnosed and treated for malignant epithelial ovarian tumours. The immunoexpression of CAS protein was assessed semiquantitatively, whereas immunoexpression of Ki-67 was performed using a computer image analysis system. Results: The immunoexpression of both CAS and Ki-67 proteins was significantly increased in the metastatic group as compared with patients without metastases. Also, a positive correlation was found between immunoexpression of Ki-67 and CAS protein, but this correlation was not significant. Conclusions: In conclusion, our data suggest that increased immunoexpression of CAS and Ki-67 proteins in serous ovarian tumours may be helpful in identifying cases of higher metastatic potential.